1990
DOI: 10.1037/0096-3445.119.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Sequential effects in magnitude scaling: Models and theory.

Abstract: Research on sequential effects in magnitude scaling is reviewed, and its implications about the adequacy of current time series regression models is discussed. A regression model that unifies what at first appear to be contradictory results is proposed. Theoretical models of judgment and perception are introduced, and their relation to alternative regression models is clarified. A theoretical model of relative judgment that clarifies the role of judgmental error and frames of reference in magnitude scaling is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
167
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(188 citation statements)
references
References 47 publications
21
167
0
Order By: Relevance
“…The idea that apparent duration depends upon the preceding stimulus is consistent with the general finding that perceptual (and non-perceptual) judgments are shaped by the previously judged Speed changes and time perception 15 item (e.g., DeCarlo & Cross, 1990;Matthews & Stewart, 2009a;Matthews & Stewart, 2009b;Ward & Lockhead, 1970), and with evidence that is more specific to time perception. For example, G.D.A.…”
Section: The Dissociation Between Judged Duration and Reproduced Durasupporting
confidence: 64%
“…The idea that apparent duration depends upon the preceding stimulus is consistent with the general finding that perceptual (and non-perceptual) judgments are shaped by the previously judged Speed changes and time perception 15 item (e.g., DeCarlo & Cross, 1990;Matthews & Stewart, 2009a;Matthews & Stewart, 2009b;Ward & Lockhead, 1970), and with evidence that is more specific to time perception. For example, G.D.A.…”
Section: The Dissociation Between Judged Duration and Reproduced Durasupporting
confidence: 64%
“…Stewart explained the pattern by modifying the RJM to include a memory for the stimulus two trials back that on some trials is used instead of the memory for the stimulus one trial back as the basis for relative judgment. Other experiments by DeCarlo and Cross (1990) and DeCarlo (1994) demonstrated that instructions significantly impact whether magnitude judgments are made relative to short-or longterm referent stimuli and responses. These findings present problems for models that rely solely on absolute or solely on relative mechanisms, requiring suitable extensions of the relative approach, as shown by Stewart, and a suitable extension of the absolute approach, as we show for SAMBA.…”
Section: Local Effects: Sequential Effect On Accuracy and Errorsmentioning
confidence: 99%
“…That is, if the previous stimulus was more intense than the current stimulus, then the subject tends to score the current stimulus as more intense. This effect is asymmetric, in that the transition from stimulus i 3 to stimulus i 5 is not the same as for i 5 to i 3 Various models for this carry-over effect have been proposed (DeCarlo and Cross, 1990), but we will consider here a model in which the effect is proportional to the magnitude difference between the prior and current stimulus:…”
Section: Carry-over Effectsmentioning
confidence: 99%